Simulation and optimization of control system operation and surface water allocation based on system dynamics modeling - Hamed Nozari (IWA Publishing, 2021)
In the present study, the performance of Dez Reservoir, its regulatory and downstream diversion dams are studied using the system dynamics method (SD) in the Vensim software. In the first step, all the effective parameters with their relationship were identified and then the simulation was carried out considering the minimum and maximum reservoir volume and downstream demand over an eight-year period (2006–2013). After model validation, the statistical indices of correlation coefficient (R2), root mean square error (RMSE), and standard error (SE) for the reservoir volume were calculated as 0.99, 3.1690, and 0.18, respectively. The statistical indices for the regulatory dam were 0.98, 7.51, and 0.13, respectively. These statistical indices were 0.92, 4.71, and 0.37 for the diversion dam. The achieved results showed that the SD-simulated releases met downstream demands and the SD method has high accuracy in simulating the performance of the surface tank system. Moreover, for a better evaluation of the results of the SD model, the eight-year Dez dam releases were optimized using the particle swarm optimization (PSO) algorithm, and the required deficiency values were evaluated in both SD and PSO models. Results showed that SD provides more appropriate planning in meeting the downstream demands than PSO. HIGHLIGHTS The performance of the system dynamics method in the management and simulation of the productivity of the water resource system for the storage reservoir, the regulatory dam, and the diversion dam was investigated simultaneously.; The accuracy of system dynamics method in the management of the mentioned integrated system was compared with that of the meta-heuristic particle swarm optimization (PSO) algorithm.;